BANK SAMPAH PERMATA DAN KONTRIBUSI SOSIAL EKONOMINYA BAGI MASYARAKAT - Arif Zunaidi; Urfiatur Rohmi Setiani; Hevia Wahyu Khotimah (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2021)
Garbage has become a problem for today's society, not only in urbanareas, in rural areas also experiencing the same thing with regard towaste. In order to solve these problems, community participation isneeded to solve the waste problem. This study focuses on themanagement of waste banks by the Kediri Bunch Youth Association(Permata). This study uses a qualitative descriptive to describe theproblems related to the theme, where the author tries to describe thesocial role of waste bank management carried out by the youth of thevillage of Tandan. As a field research, this research shows that socially,this waste management activity has been successful, while in theeconomic sector, although it is less significant in providing income for thecommunity, it has succeeded in increasing village income which is thenused to buy seeds and distributed to the people of the Tandan hamlet.